MODERATION IN FALAK: Respond on the Variaty of Month Arrival Determination - HL, Rahmatiah (Al-Risalah Jurnal Ilmu Syariah dan Hukum, 2021)
This study aims to elaborate the maslahah mursalah theory in responding to differences in the determination of the beginning of the Hijri month in religious moderation and examining the idea of wujū al - hilāl, rukyat al-hilāl and Imkān al-Rukyat theory in the analysis of religious moderation. The research method employes comparative study. A comparative study is comparing one idea to another and the results of one research with other tasks. The results showed that hisab and rukyah combination is possible to practice in Indonesia to create benefits based on maslahah mursalah. The maslahah mursalah approach is used to formulate laws based on maslahat considerations, a priority in maqasid al-sharia. The use of maslahah mursalah can be agreed upon. Besides, the Indonesian Muslim Ummah should be together in the implementation of worship for the sake of achieving a strong Islamic ukhuwah. Religious moderation is crucial to bridge the differences in determining the beginning of the Hijri month. The Falak science experts in charge of this issue are responsible for formulating the criteria for determining the beginning of the Hijri month, mainly related to fasting. 01 Ramadan, Eid on 01 Shawwal and 10 Zulhijjah, which can be accepted by those who use the criteria of rukyat al- hilāl and wujūd al-hilāl. In this way, efforts towards the unification of the Hijriyah calendar can be realized.